Validation of a Real-Time PCR for the Detection of Mycobacterium tuberculosis Complex Members in Bovine Tissue Samples - Lorente-Leal, Victor; Liandris, Emmanouil; Castellanos, Elena; Bezos, Javier; Domínguez, Lucas; de Juan, Lucía; Romero, Beatriz (Frontiers in Veterinary Science, 2019)
Although the post-mortem diagnosis of bovine tuberculosis is mainly achieved through microbiological culture, the development of other techniques to detect Mycobacterium tuberculosis complex (MTBC) members directly from tissue samples has been pursued. The present study describes the development, optimization and validation of a Real-Time PCR based on the mpb70 gene to detect MTBC members in clinical tissue samples from cattle. Specific primers and a hybridization probe were used to amplify MTBC-specific sequences in order to avoid cross-reaction with non-MTBC species. An Internal Amplification Control (IAC) was included in order to assess the presence of PCR inhibitors in the samples. The PCR was optimized to achieve maximum efficiency, and the limit of detection, limit of quantification and dynamic range of the reaction were determined. The specificity of the reaction was tested against 34 mycobacterial and non-mycobacterial species. The diagnostic sensitivity, specificity and positive and negative predictive values (PPV and NPV) of the method were assessed on 200 bovine tissue samples in relation to bacteriological culture. The dynamic range of the reaction spanned from 5ng/reaction (106 genome equivalents) to 50fg/reaction (10 genome equivalents). The efficiency of the reaction was 102.6% and the achieved R2 was 0.99. The limit of detection with 95% confidence was 10 genome equivalents/reaction. No cross-reactions with non-MTBC species were observed. The diagnostic sensitivity and specificity values of the mpb70 specific Real-Time PCR respect to culture were 94.59% (95% CI: 86.73% to 98.51%) and 96.03% (95% CI: 90.98% to 98.70%), respectively, with a PPV of 93.33% (95% CI: 85.55% to 97.07%) and a NPV of 96.80 % (95% CI: 92.10% to 98.74%). The concordance of the Real-Time PCR based on mpb70 is comparable to that of culture (K=0.904) showing a great potential for the detection of members of the MTBC in animal tissues.